Sets of regular systems of divisors of a generalized integer - Porubský, Štefan (Annales Mathematicae Silesianae, 1998)
The notion of a regular system of divisors of a number underlying a Narkiewicz's idea of the generalization of the familiar Dirichlet and unitary convolution of arithmetical functions is used to extend some combinatorial results about systems of subsets of divisors of a generalized integer.